2020
DOI: 10.1002/ece3.6271
|View full text |Cite
|
Sign up to set email alerts
|

Studies on reproductive strategies of Vitex negundo L. var. heterophylla (Franch.) Rehder (Lamiaceae) based on morphological characteristics and SSR markers

Abstract: Vitex negundo L. var. heterophylla (Franch.) Rehder (Lamiaceae) is an important tree species for soil and water conservation, yet the reproductive ecology of this species remains to be elucidated. To investigate the reproductive traits of V. negundo var. heterophylla, the phenology, morphological characteristics (a suite of characters was assessed: floral morphology, nectar production, pollen viability, and stigma receptivity) and mating system of this species were systematically revealed for the first time in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 41 publications
3
12
0
1
Order By: Relevance
“…heterophylla is a constantly 25%, which means that only one of the four ovules can fully develop and bear fruit, and the other three will be aborted due to late zygotic competition. The same phenomenon is found in V. fischeri (Lengkeek et al, 2006) and V. Doniana (Sinebou et al, 2016) is also reported. This is not due to pollen limitation, but may be related to resource allocation.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…heterophylla is a constantly 25%, which means that only one of the four ovules can fully develop and bear fruit, and the other three will be aborted due to late zygotic competition. The same phenomenon is found in V. fischeri (Lengkeek et al, 2006) and V. Doniana (Sinebou et al, 2016) is also reported. This is not due to pollen limitation, but may be related to resource allocation.…”
Section: Discussionsupporting
confidence: 85%
“…Vitex negundo L. var. heterophylla has a bilabial flower that is symmetrical, and the lower lip of the bilabial corolla is flat and broad, which can be used as a comfortable platform for insects to forage (Sun et al, 2020). A similar situation also occurred in Thalictrum pubescens, an ambophilous (both zoophily and anemophily) species that probably represents a transitional state in the evolution of anemophily.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…heterophylla can produce mature fruits under both outcrossing (the highest fruit-setting rate) and selfing strategies, indicating that V. negundo L. var.heterophylla presents a mixed mating system with mainly outcrossing and self-compatibility. It is consistent with the conclusion of Sun et al (2020) based on the hybridization index and pollen ovule ratio.…”
Section: Discussionsupporting
confidence: 91%
“…Bagging is carried out at the bud stage, and according to the pollen vigor and stigma pollination at different stages after flowering, and the best pollination time is determined to be from 10:00 am to 12:00 am (Sun et al, 2020). With the help of tweezers, the anther directly contacts the stigma for pollination.…”
Section: Artificial Pollination Experimentsmentioning
confidence: 99%